Performance Optimization of Synchronous Reluctance Motor using Adaptive MTPA Curve Fitting with Anti-Windup Current Control - Alex V; Rammohan A (Results in Engineering)
Synchronous Reluctance Motors have gained increasing attention in modern electric drive applications due to their high efficiency, robustness, and magnet-free rotor design. However, achieving optimal performance requires effective control strategies, particularly for torque maximization. Maximum torque per ampere is a widely used technique to ensure efficient operation by minimizing motor current for a given torque. This work presents the maximum torque per ampere-based control strategy for a synchronous reluctance motor using a curve fitting algorithm to approximate the current and torque trajectory in real time. This control strategy is essential for improving the efficiency and dynamic performance of the synchronous reluctance motor by optimizing the stator current vector for maximum torque production at minimal current. Conventional scalar control methods typically rely on precomputed lookup tables or iterative optimization algorithms, which introduce computational overhead and require significant memory resources. In this study, a curve-fitting approach integrated with anti-windup control is employed, where an analytical function is developed to closely approximate the optimal current trajectory. This method effectively minimizes computational burden while preserving high control accuracy. The proposed method derives a mathematical model based on the motor torque equation, where the optimal d-axis and q-axis current components are expressed as a function of motor parameters, including inductances, rotor position, and torque demand. The curve fitting equation is embedded within the controller, enabling fast and efficient computation of optimal current references without iterative calculations or extensive memory storage.